The evaluation of the effect of Acid Buf™ on stomach ulcer occurrence, growth performance and histological parameters of grower - finisher pigs - Steenkamp, Jan Adriaan (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScAgric)--Stellenbosch University, 2014.